KAJIAN PEMANFAATAN SEKAM PADI DIFERMENTASI Aspergillus niger DALAM RANSUM DISUPLEMENTASI TEPUNG DAUN UBI JALAR UNGU (Ipomoea batatas, L.) TERHADAP PENAMPILAN ITIK BALI UMUR 24 -36 MINGGU - T. G. O., SUSILA; YADNYA, T. G. B.; TRISNADEWI, A. A. A. S. (Majalah Ilmiah Peternakan; Vol 21 No 2 (2018): Vol 21, No 2 (2018)DO - 10.24843/MIP.2018.v21.i02.p01, 2018)
The experiment was carried out to study the effect on fermented rice hull in diets supplemented with purple sweet potato (Ipomoea batatas L.) leaves meal on performance of bali ducks. A completely randomized design with five treatments such as diet without rice hull (A), diet contaning 10% rice hull (B), diet containing 10% fermented rice hull (C), ration contaning 9% rice hull and 1% purple sweet potato leaf meal (D), diet containing 9% fermented rice hull and 1% purple sweet potato leaf meal (E). Each treatment in three replications consists of 5 female ducks. The variables observed were feed consumption, antioxidant capacity, total egg weight and FCR, and total eggs, egg production per day, and means of eggs weight. It showed that diet feed consumption of ducks fed E treatment found 3.32% lower (P<0,05), total eggs 47,56% higher (P<0,05) compared to A. In addition, E treatment can increase total amount of eggs, egg production per day, and 29,16%, 29,15% dan 12,12% means of eggs (P<0,05) compared to A treatment. It can be concluded that ducks fed diets containing fermented rice hull and purple sweet potato leaf meal supplemented can improve efficiency of diets and production of eggs.